EFEKTIVITAS PROGRAM TEMPAT PENGOLAHAN SAMPAH TERPADU (TPST) DI DESA WEDOROKLURAK KABUPATEN SIDOARJO - Adinda Oktavia Cantika Putri; Hendra Sukmana (LPPM Universitas Abdurrab, 2026)
This study aims to analyze and describe the effectiveness of the Integrated Waste Processing Facility (TPST) program in Wedoroklurak Village, Sidoarjo Regency. The methodology used is qualitative with a descriptive approach that aims to collect and describe information, data, and various problems in depth through field observations using a purposive sampling method carried out by selecting subjects based on specific objectives. The results of this study use the concept of effectiveness theory according to Campbell reviewed from 5 indicators including: first, the indicator of program success can be concluded that the program implementation has been running systematically with a clear flow, but there are obstacles such as weak management and coordination in the implementation of this program. Second, the indicator of target success, in this program the targets include households, small business actors, and public facilities that are sources of daily waste by providing socio-economic. Third, the program satisfaction indicator demonstrates that the TPST is capable of providing waste management services that directly benefit the community, improving the quality of life for the community. Fourth, the input and output level indicator demonstrates a balance between input and output because the resources used successfully produce outputs in accordance with the program's objectives. Fifth, the overall goal achievement indicator indicates that the program can be said to be quite successful in realizing its overall objectives, although institutional strengthening and consistent community participation are still needed to maintain the program's sustainability.